"Choice" and place of delivery: a qualitative study of women in remote and rural Scotland. Issue 1 (9th February 2009) - Pitchforth, E; van Teijlingen, E; Watson, V; Tucker, J; Kiger, A; Ireland, J; Farmer, J; Rennie, A-M; Gibb, S; Thomson, E; Ryan, M
Abstract : Objective: To explore women's perceptions of "choice" of place of delivery in remote and rural areas where different models of maternity services are available. Setting and methods: Remote and rural areas of the North of Scotland. A qualitative study design involved focus groups with women who had recent experience of maternity services. Results: Women had varying experiences and perceptions of choice regarding place of delivery. Most women had, or perceived they had, no choice, though some felt they had a genuine choice. When comparing different places of birth, women based their decisions primarily on their perceptions of safety. Consultant-led care was associated with covering every eventuality, while midwife-led care was associated with greater quality in terms of psycho-social support. Women engaged differently in the choice process, ranging from "acceptors" to "active choosers." The presentation of choice by health professionals, pregnancy complications, geographical accessibility and the implications of alternative places of delivery in terms of demands on social networks were also influential in "choice." Conclusions: Provision of different models of maternity services may not be sufficient to convince women they have "choice." The paper raises fundamental questions about the meaning of "choice" within current policy developments and calls for a more critical approach to the use of choice as a service development and analytical concept.